A new species of Tardigrada (Eutardigrada: Macrobiotidae) from Iberian Peninsula and Canary Islands (Spain) - Guil, Noemí; Guidetti, Roberto (Zootaxa, 2005)
Minibiotus gumersindoi n. sp. is described. This species was collected on a granite mountain range in Sierra de Guadarrama (Bustarviejo valley, Embalse de la Jarosa and Cercedilla, Madrid, Spain) and on a volcanic island in Parque Natural Caldera de Taburiente (La Palma, Canary Islands, Spain). This new species is characterized by a unique set of characters in the genus: the presence of large round pores in the body and a larger round pore at the distal part of each leg. New records of several known species, for Madrid, Canary Islands and/or the Iberian Peninsula are given.